Sustainable Membrane Technologies for Environmental and Industrial Applications: A Review - Tahseen Khan, (International Journal of Membranes, 2025)
Membrane-based technologies have become indispensable in addressing global environmental and industrial challenges, including water scarcity, pollution control, and energy efficiency. While conventional membranes provide high selectivity and process efficiency, their sustainability is limited by factors such as fouling, high energy consumption, and end-of-life waste management. Recent advances in material science, nanotechnology, and bio-inspired design have led to the emergence of sustainable membranes with improved durability, lower environmental footprint, and broader application potential. This review explores the fundamental principles of sustainable membrane science, recent innovations in green materials, and their role in environmental and industrial applications. Case studies in water and wastewater treatment, desalination, air purification, and resource recovery highlight the transformative potential of sustainable membranes. Additionally, industrial applications in food, pharmaceuticals, energy, and petrochemicals are critically examined. Finally, limitations, policy considerations, and future research directions are discussed. The review concludes that sustainable membrane technologies are positioned as central solutions in the transition to a circular economy, offering pathways for eco-friendly industrial growth and environmental protection.
Keywords: Environmental applications; Industrial Processes; nanotechnology; resource recovery; sustainable membranes